Integrasi Astronomi dalam Ilmu Falak di PTAI dan Pondok Pesantren - Siti Tatmainul Qulub (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
This article examines the integration of science between astronomy and Islamic astronomy in Islamic Higher Education (UIN Walisongo Semarang) and Islamic Boarding Schools (Islamic Boarding School al-Mubarok Lanbulan Madura). Data was collected through in-depth interview techniques about curriculum and learning at Islamic College and Islamic Boarding Schools, and equipped with other reading materials. The results showed that the integration of Astronomy in Islamic astronomy in UIN Walisongo Semarang already existed, but not all were implemented perfectly. At the philosophical, material, and methodology level can be said to have been implemented a lot. However, implementation at the strategy level is still lacking. This can be seen from the competence of permanent lecturers who are almost all fiqh. The integration of Astronomy in Islamic astronomy at al-Mubarok Lanbulan Madura is still not visible, both at the philosophical, material, and strategy levels. However, at the methodology level, the method used is based on a science study methodology that is implemented in the writing of santri scientific papers.